Can "pain matrix" be convinced to feel more pain? Looking for a neurophysiological marker of nocebo effect. Issue 3 (March 2016) - Pazzaglia, C.; Testani, E.; Padua, L.; Valeriani, M.
Abstract : Objectives: To investigate whether the expectation of feeling more pain modifies laser evoked potential (LEP) amplitude and laser-pain rating. Methods: Twenty subjects were recruited: 10 in a verbal suggestion session (VSS) and 10 in a conditioning session (CS). At time 0, LEPs were acquired from 31 scalp electrodes to right and left hand stimulation. At time 1, Vaseline was applied on the right hand and subjects were informed that they were receiving a hyperalgesic cream. In VSS, LEPs were recorded using the same stimulus intensity as in the baseline. In CS, LEPs were recorded initially to a stimulus of surreptitiously increased intensity, in order to make the subjects believe that the treatment worked. Then, Vaseline was applied again and LEPs were recorded at the same stimulus intensity as in the baseline. Results: In VSS, laser-pain rating was increased after treatment. In both VSS and CS, the fake treatment did not produce any increase of both N2 and P2 amplitudes. No topographical modification was observed. Conclusions: The expectation of feeling more pain increases the laser-pain rating, but not the LEP amplitude. Key message: The subjective evaluation of pain is integrated in a more complex brain network than that generating LEPs.